MODEL HIPOTESIS PENERAPAN SATUAN KREDIT KOMPETENSI (SKK) PADA PROGRAM PENDIDIKAN KESETARAAN - Supriyono Supriyono (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
Based on the regulation of Minister of National Education, No. 14 of 2007 about the standard content for the program of A, B, and C packages, the attainment of learning achievement competence, named as the unit of competence credit (SKK) has been regulated. The system of SKK at equivalency is education in different from semester credit system (SKS) at higher education. This article discusses SKK introducing an implementation model by distributing the learning loads on each competence unit or sub unit into SKK unit. SKK system will enable to implement various flexibility competence and excellence competence of nonformal education. Besides, several learning models in nonformal education can be integrated in one interconnected system, i.e. SKK and national examination of equivalency education.